The Effect Of Location And Product Quality On Consumer Purchase Interest (Study On Msme Kaf Fried Chicken Jombang) - Shofwan, Ali Muhammad; Pancaningrum, Erminati (CV. Utility Project Solution, 2023)
This study aims to examine the effect of location and product quality on consumer buying interest at MSME KAF Fried Chicken Jombang. Quantitative research method, by collecting data in the field using the questionnaire method. The research population consisted of all KAF Fried Chicken Jombang MSME consumers, with a sample of 100 consumers. Data analysis was performed using inferential analysis method, as well as testing the hypothesis and the coefficient of determination. Based on the results of the study, it was found that there was a positive and significant influence between location and consumer buying interest at KAF Fried Chicken. That is, the more strategic the location, the higher consumer buying interest tends to be. In addition, a positive and significant influence was found between product quality and consumer buying interest at KAF Fried Chicken. High product quality has the potential to influence consumers to buy products. Thus, this study concludes that location and product quality play an important role in increasing consumer buying interest at MSME KAF Fried Chicken Jombang.